Methods of Complex Testing of Multiple Soil Properties in Laboratory and Field Conditions - Xonkeldiev M.M; Ochilov A.E; Mamatov E.M (Zien Journals, 2023)
The paper covers the problem of the lardier estimation of such properties as relative swelling, relative shrinkage and appearance of ground pressures, which can be observed in laboratory conditions in swelling pressures.
Keywords: Swelling soils; relative swelling; relative shrinkage; swelling pressures